2017
DOI: 10.1186/s12885-017-3246-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen receptor β agonists on proliferation and gene expression of ovarian cancer cells

Abstract: BackgroundEstrogen receptor (ER) β has been suggested to affect ovarian carcinogenesis. We examined the effects of four ERβ agonists on proliferation and gene expression of two ovarian cancer cell lines.MethodsOVCAR-3 and OAW-42 ovarian cancer cells were treated with the ERβ agonists ERB-041, WAY200070, Liquiritigenin and 3β-Adiol and cell growth was measured by means of the Cell Titer Blue Assay (Promega). ERβ expression was knocked down by transfection with specific siRNA. Additionally, transcriptome analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 62 publications
1
36
0
1
Order By: Relevance
“…We then focused on exploring the effect of compound 3 on the histone acetylation and gene expression in IGROV1. At 6 h of treatment, compound 3 induces an increase of acetylated H4 isoforms ( Figure 5 ) and a downregulation of MYC and CCND1 genes ( Figure 6 a), acting as an ERβ agonist, in accordance with other findings on other agonists [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…We then focused on exploring the effect of compound 3 on the histone acetylation and gene expression in IGROV1. At 6 h of treatment, compound 3 induces an increase of acetylated H4 isoforms ( Figure 5 ) and a downregulation of MYC and CCND1 genes ( Figure 6 a), acting as an ERβ agonist, in accordance with other findings on other agonists [ 30 , 31 ].…”
Section: Discussionsupporting
confidence: 87%
“…It has previously been reported that ERβ mediates ovarian cancer cell growth repression by decreasing the cellular content of, among others, retinoblastoma, phospho-AKT, cyclin D1, and A2 as well as upregulating the cyclin-dependent kinase inhibitor p21 13 , 14 , 26 , 27 . In this report we have focused on other aspects of ERβ function and activity as a ligand-activated transcription factor and growth inhibitor of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro, we showed reduced proliferation and migration of ovarian cancer cells after overexpression of ERβ as well as increased rates of apoptosis [ 12 ]. Moreover, we found a significant growth-inhibition of ovarian cancer cells by treatment with specific ERβ-agonists [ 13 ]. Thus, these data support the tumor suppressive role of ERβ in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies clearly suggest a tumor suppressive role of ERβ in ovarian cancer as it has been shown for breast or prostate cancer [ 9 11 ]. Our group demonstrated that ERβ reduces proliferation and migration, but activates apoptosis of ovarian cancer cells [ 12 ] and that specific ERβ-agonists significantly inhibit growth of different ovarian cancer cell lines [ 13 ]. Furthermore, our results from a phenotype-genotype association study suggested that the single nucleotide polymorphism rs3020449 in the promoter region of ESR2 gene might affect progression of ovarian cancer [ 14 ].…”
Section: Introductionmentioning
confidence: 99%